Traffic-Aware Channel Assignment for Multi-Radio Wireless Networks - DA SILVA, LUIZ (My University, 2012)
This paper studies channel assignment in multi-hop wireless networks in which nodes are equipped with multiple radios, each of which can be assigned to a channel. We argue for an approach that rst assigns channels independently of tra c, to achieve basic connectivity and support light loads such as control tra c, and then dynamically assigns channels to the remaining radios in response to tra c demand. The objective is to balance the need for a stable baseline topology and the desire to maximize throughput by dynamically adapting the topology to current network conditions. We call this a tra c-aware (TA) approach, in contrast to both tra c-independent (TI) and tra c-driven (TD) channel assignment and topology control schemes found in the literature. We formulate the problem as a two-stage mixed integer linear program (MILP), and nd that our approach supports good connectivity and data rates comparable to those achieved with a TD channel assignment, while achieving lower resource utilization than TI approaches. We also quantify the tradeos involved in the decision of what proportion of radios to enable during the tra c-independent stage and what proportion to enable dynamically in response to changing tra c demands
Lecture Notes in Computer Science
Networking 2012
PUBLISHED
Prague, Czech Republic
Keywords: Wireless Networks; Telecommunications